A secondary battery and an electric device including the same

CN122800623APending Publication Date: 2026-09-22HEFEI GUOXUAN HIGH TECH POWER ENERGY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611282018.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-24
Publication Date
2026-09-22

AI Technical Summary

Technical Problem

[0004]针对目前锂离子电池存在的问题,本申请提供了一种二次电池以及相关的用电设备

Benefits of technology

本申请的二次电池通过控制负极SEI膜中硫元素所存在的两种类型的配比,优化了负极界面膜的组成和结构,获得了致密、稳定、高离子导电的界面膜,提高了电池快充倍率性能,同时,还有效抑制了电解液与负极活性材料的持续性副反应,降低了电解液的消耗速率,进而改善了二次电池的常温循环性能、高温存储性能及高温稳定性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122800623A_ABST
    Figure CN122800623A_ABST
Patent Text Reader

Abstract

The application relates to the field of power batteries and energy storage, in particular to a secondary battery and an electric device comprising the same. The secondary battery comprises a positive electrode, a negative electrode and an electrolyte, the negative electrode comprises a negative electrode active material layer and an SEI film on the surface of the negative electrode active material layer, the SEI film contains Li2SO x and lithium organic sulfonate RSO3Li, wherein x is 3 or 4, R is C1-C6 alkyl or alkenyl, and the percentage content of sulfur elements in Li2SO x is S1%, the percentage content of sulfur elements in the lithium organic sulfonate RSO3Li is S2%, 1<=S1 / S2<=2.5, and the negative electrode tab OI value w and S1 / S2 satisfy 1<=10w-S1 / S2<=2. Through controlling the sulfur element content ratio of different sulfur-containing components in the negative electrode SEI film and synergistically controlling the negative electrode OI value, the secondary battery simultaneously has excellent fast charging capacity, long cycle life and reliable high-temperature stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the fields of power batteries and energy storage, specifically to a secondary battery and an electrical device containing the same. Background Technology

[0002] Lithium-ion rechargeable batteries, with their advantages of high energy density, long cycle life, and no memory effect, have become the core power source for portable electronic devices, power tools, and new energy vehicles. However, with the increasing demand for fast charging, ensuring thermal safety and cycle life while improving fast charging performance has become a key technological bottleneck restricting the industry's development. There is an inherent contradiction between fast charging performance and thermal safety. To achieve fast charging, the battery needs to withstand high current surges, requiring the use of electrolytes with high conductivity. These electrolytes often use low-viscosity ethyl acetate solvents, but their electrochemical and thermal stability are poor, and they are prone to decomposition and gas generation at the negative electrode at high temperatures. Simultaneously, the negative electrode of fast-charging batteries has higher activity, and surface side reactions are significantly amplified at high temperatures, further deteriorating thermal safety. To address these issues, research has shown that sulfur-based additives can form a solid electrolyte interphase (SEI) film with a special composition on the negative electrode surface. This SEI film possesses excellent thermal stability and ion conductivity, effectively suppressing high-temperature side reactions of the electrolyte on the negative electrode surface, thereby improving the high-temperature performance of fast-charging batteries, extending their lifespan, and enhancing safety. However, the method of constructing an interfacial film using conventional electrolyte additives often weakens the fast-charging capability due to increased interfacial impedance.

[0003] Therefore, developing a new type of rechargeable battery that combines excellent fast charging capability, reliable high-temperature stability, and long-cycle stability has significant academic value and promising industrial application prospects. Summary of the Invention

[0004] To address the current problems of lithium-ion batteries, this application provides a secondary battery and related electrical devices. The secondary battery of this application controls the Li₂SO₄ content in the solid electrolyte interphase (SEI) film formed on the surface of the negative electrode active material layer. x The ratio of (x=3 or 4) to sulfur in organic lithium sulfonate RSO3Li improves the fast-charge cycle life, high-temperature storage performance, and high-temperature stability of the secondary battery.

[0005] The specific technical solution of the present invention is as follows: In a first aspect, the present invention provides a secondary battery comprising a positive electrode, a negative electrode, and an electrolyte, wherein the negative electrode comprises a negative electrode active material layer and an SEI film located on the surface of the negative electrode active material layer, the SEI film containing Li₂SO₄. x And organic lithium sulfonates RSO3Li, Li2SO x In Li₂SO₃Li, x is 3 or 4, and R is a C1-C6 alkyl or alkenyl group.x The sulfur content in the medium is S1%, and the sulfur content in RSO3Li is S2%, where 1 ≤ S1 / S2 ≤ 2.5. The OI value of the negative electrode is w, where 1 ≤ 10w-S1 / S2 ≤ 2. When this value < 1, the ion transport capacity of graphite is low, and the fast-charging performance of the battery will deteriorate; when this value > 2, the stability of the SEI film on the graphite surface will decrease, thereby shortening the cycle life of the battery. Controlling 10w-S1 / S2 within the range of 1 to 2 can achieve the optimal balance between fast-charging performance and cycle life.

[0006] Furthermore, 0 < S1 ≤ 10; 0 < S2 ≤ 4. When S1 and S2 fall within the above range, an SEI film with both good thermal stability and ion conductivity can be formed on the negative electrode surface, effectively avoiding the problem of excessive SEI film impedance due to excessive sulfur content leading to deterioration of fast charging performance, or insufficient sulfur content failing to adequately protect the negative electrode surface.

[0007] Furthermore, 1≤S1≤5; 0<S2≤2. By further limiting S1 and S2 within the above ranges, a better SEI film structure can be obtained, which can further improve lithium-ion transport efficiency while ensuring high-temperature stability, thereby better balancing the battery's fast-charging performance and high-temperature cycle life.

[0008] Furthermore, 0.25 ≤ w ≤ 0.40. When the OI value is too low, the graphite's ion transport capacity is insufficient, leading to deterioration in fast-charging performance; when the OI value is too high, the anisotropy of graphite increases, and volume changes cause the SEI film to rupture, reducing cycle life. Controlling the OI value within the range of 0.25~0.40 can simultaneously balance fast-charging performance and cycle life.

[0009] In some implementations, the OI value of the negative electrode is 0.25-0.38.

[0010] In some implementations, the OI value of the negative electrode is 0.30-0.35.

[0011] In some embodiments, the porosity of the negative electrode is 21%, 22%, 24%, 26%, 28%, 29%, 30%, 31%, 32%, 33%, 34%, 35%, 36%, 37%, 38%, 39%, 40%, or any combination of these values.

[0012] Li2SO4 in SEI membrane xComponents such as (x=3 or 4) exhibit high thermal stability, which can suppress the decomposition of the SEI film at high temperatures, reduce continuous side reactions between the electrolyte and the negative electrode, inhibit gas production, and increase the density and electrochemical stability of the SEI film, thereby improving the cycle performance and safety performance of the secondary battery, especially its high-temperature cycle performance and storage performance. However, since both of these lithium salts are poor conductors of lithium ions and electrons, a high content of them can lead to a higher impedance of the SEI film, thus affecting the battery's kinetic performance and ultimately degrading its fast-charging performance. Furthermore, while the organic lithium sulfonate (RSO3Li) in the SEI film is beneficial for lithium ion transport and fast-charging performance, excessive content can easily cause swelling with the electrolyte at high temperatures, leading to the electrolyte penetrating the SEI and reacting with the negative electrode, thus degrading the battery's high-temperature performance. In conclusion, maintaining both within a reasonable range can simultaneously ensure both fast-charging and high-temperature performance of the battery. Furthermore, increasing the OI value of graphite improves the material's ionic conductivity, facilitating rapid lithium-ion transport and thus enhancing the fast-charging performance of the graphite anode. However, increased OI also enhances material anisotropy, leading to greater volume changes during lithium-ion insertion / extraction. This repeated mechanical stress can cause the SEI film covering the graphite surface to crack, reducing the cycle life of the lithium-ion battery. Therefore, the OI value needs to be within a reasonable range to balance fast charging and long battery life. A relationship was established between the presence and content of sulfur on the graphite surface (S1, S2) and the OI value w: 10w - S1 / S2. When this value < 1, the ion transport capacity of graphite is low, and the fast-charging performance of the battery deteriorates. Conversely, when this value > 2, the stability of the SEI film on the graphite surface decreases, thereby shortening the battery's cycle life. Finally, the values ​​of S1 and S2 are also affected by w. When w increases, the sulfate ester additive is completely reduced on the graphite surface, resulting in an increase in S1 and a decrease in S2. S1, in turn, improves the high-temperature stability of the SEI film on the graphite surface, thereby alleviating the problem of SEI film instability after w increases. The two influence each other and need to be maintained within a reasonable range in order to achieve a balance of optimal battery performance.

[0013] Furthermore, the electrolyte includes a sulfur-containing additive, which includes at least one selected from sulfonates, sulfates, sulfites, polycyclic cyclic sulfates, and polycyclic sulfites. These sulfur-containing additives can improve the composition and structure of the interfacial film, enabling it to more effectively exert the aforementioned effects, thereby further improving the cycle performance and storage performance of the secondary battery.

[0014] Furthermore, the sulfonate ester includes at least one of the compounds shown in Formula I-1 and Formula I-2. Formula I-1, Formula I-2, In Formula I-1, Q1 and Q2 are independently selected from C1-C6 alkylene groups; In Formula I-2, R1 and R2 are independently selected from hydrogen atoms or C1-C6 alkyl groups, and Q3 is selected from C1-C6 alkylene groups or C2-C6 alkenyl groups.

[0015] In some embodiments, Q1 and Q2 are independently selected from C1-C4 alkylene groups, such as methylene, ethylene, or propylene.

[0016] In some embodiments, the sulfonate includes at least one of methylene disulfonate (MMDS), ethyl disulfonate, and propylene disulfonate.

[0017] In some embodiments, in Formula I-2, R1 and R2 are independently selected from hydrogen atoms or C1-C4 alkyl groups, and Q3 is selected from C1-C4 alkylene groups or C2-C4 alkenyl groups.

[0018] In some embodiments, the sulfonate includes at least one of 1,3-propanesulfonyl lactone (PS), 1-propylene-1,3-sulfonyl lactone (PST), and 1,4-butanesulfonyl lactone (BS).

[0019] Furthermore, the sulfate ester includes at least one of the compounds shown in Formula I-3. Formula I-3 In Formula I-3, R3, R4, R5, and R6 are independently selected from hydrogen atoms or C1-C6 alkyl groups, and Q4 is absent or selected from C1-C6 alkylene groups.

[0020] In some embodiments, in formulas I-3, R3, R4, R5, and R6 are independently selected from hydrogen atoms or C1-C4 alkyl groups, and Q4 is absent or selected from C1-C4 alkylene groups.

[0021] In some embodiments, in Formula I-3, R3, R4, R5, and R6 are independently selected from hydrogen atoms, methyl, ethyl, n-propyl, or isopropyl, and Q4 is absent.

[0022] In some embodiments, the sulfate ester includes at least one of vinyl sulfate (DTD), 4-methyl ethylene sulfate (PCS), 4-ethyl ethylene sulfate (PES), 4-propyl ethylene sulfate (PEGLST), and propylene sulfate (TS).

[0023] Furthermore, the sulfite comprises at least one of the compounds shown in Formula I-4 and Formula I-5. Formula I-4, Formula I-5, In Equation I-4, R7, R8, R9, R10 Independently selected from hydrogen atoms or C1-C6 alkyl groups, Q5 is absent or Q5 is selected from C1-C6 alkylene groups; in formulas I-5, R 11 and R 12 It is independently selected from C1-C6 alkyl groups.

[0024] In some embodiments, the sulfite includes ethylene sulfite (DTO).

[0025] In some embodiments, in formulas I-5, R11 and R12 are independently selected from C1-C4 alkyl groups.

[0026] In some embodiments, the sulfite includes at least one of dimethyl sulfite (DMS) and diethyl sulfite (DES).

[0027] Furthermore, the polycyclic sulfides and / or polycyclic sulfites include at least one of the compounds shown in formulas I-6 to I-11.

[0028] In formulas I-6~I-11, R 13 ~R 24 It is independently selected from hydrogen atoms or C1-C6 alkyl or C1-C6 alkenyl groups.

[0029] Furthermore, the sulfonate ester includes at least one selected from methyl disulfonate, ethyl disulfonate, propylene disulfonate, 1,3-propane sulcolone, 1-propylene-1,3-sulfonate lactone, and 1,4-butane sulcolone, and / or the sulfate ester includes at least one selected from vinyl sulfate, 4-methyl ethylene sulfate, 4-ethyl ethylene sulfate, 4-propyl ethylene sulfate, and propylene sulfate, and / or the sulfite ester includes at least one selected from ethylene sulfite, dimethyl sulfite, and diethyl sulfite.

[0030] Furthermore, the polycyclic cyclic sulfates and / or polycyclic sulfites include at least one of pentaerythritol bicyclic sulfate (TDT), 4,4'-bis-1,2-oxothiane, 2,2,2',2'-tetraoxide (Bi-PS), glyoxal sulfate (D-DTD), ethylene disulfate (Bi-DTD), ethylene trisulfate (T-DTD), and mannitol carbonate ethylene sulfate (EC2DTD).

[0031] The structural formula is:

[0032] Furthermore, based on the mass of the electrolyte, the mass content of the sulfur-containing additive is 0.5%-4%.

[0033] In some embodiments, the electrolyte further includes other additives, including at least one selected from vinylene carbonate (VC), ethylene ethylene carbonate (VEC), lithium difluorophosphate (LiDFP), lithium fluorosulfonate (LiFS), fluoroethylene carbonate (FEC), tris(trimethylsilane) phosphate (TMSP), tris(trimethylsilane) borate (TMSB), difluoroethylene carbonate, trifluoropropylene carbonate, methyl ethyl 2,2,2-trifluorocarbonate, diethyl 2,2,2-trifluorocarbonate, tris(trifluoroethyl) phosphate, and 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether.

[0034] Furthermore, the electrolyte also includes other additives, including at least one of vinylene carbonate, ethylene ethylene carbonate, lithium difluorophosphate, and fluoroethylene carbonate; the mass content of the other additives is 0.1%-10% based on the mass of the electrolyte.

[0035] In some embodiments, the other additives are present in a mass content of 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 6%, 7%, 8%, 9%, or any combination of these values. In some embodiments, the other additives are present in a mass content of 0.1%-5%.

[0036] Furthermore, the electrolyte comprises a carbonate solvent and a low-viscosity solvent; the carbonate solvent comprises at least one of ethylene carbonate (EC), dimethyl carbonate (DMC), and ethyl methyl carbonate (EMC); the low-viscosity solvent has a viscosity ≤0.6 cP and is selected from at least one of carboxylic acid ester solvents and nitrile solvents; the low-viscosity solvent comprises at least one of methyl acetate, ethyl acetate, ethyl propionate, and acetonitrile. Using a low-viscosity solvent helps improve the conductivity of the electrolyte and enhances the wettability of the electrolyte to the electrode, thereby improving the fast-charging performance of the battery. However, low-viscosity solvents (such as ethyl acetate) have poor electrochemical and thermal stability, and are prone to decomposition and gas generation at the negative electrode at high temperatures. This application forms a stable SEI film on the negative electrode surface using sulfur-containing additives, which can effectively suppress high-temperature side reactions of low-viscosity solvents on the negative electrode surface, thereby improving fast-charging performance while ensuring high-temperature stability.

[0037] In some embodiments, the electrolyte further includes an electrolyte lithium salt, the lithium salt comprising at least one selected from lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium trifluoromethanesulfonate (LiOTf), lithium bis(fluoromalonic acid)borate (LiBOB), lithium bis(fluoromalonic acid)borate (LiBFMB), and lithium difluorooxalateborate (LiDFOB).

[0038] In some embodiments, the lithium salt may further include at least one of lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethylsulfonyl)imide (LiTFSI), lithium bis(pentafluoroethylsulfonic acid)imide (LiBETI), lithium (trifluoromethylsulfonyl)(perfluorobutylsulfonyl)imide (LiFNFSI), and lithium 4,5-dicyano-2-(trifluoromethyl)imidazolium (LiTDI).

[0039] Furthermore, the electrolyte comprises LiPF6 and LiFSI, and satisfies N (LiPF6) >N (LiFSI) 0.8M≤N (LiPF6) +N (LiFSI) ≤1.5M, 0<N (LiFSI) <0.4M, where N (LiPF6) and N (LiFSI) The values ​​represent the molar concentrations of LiPF6 and LiFSI based on the electrolyte, respectively. Using LiFSI in combination with LiPF6 maintains the passivation protection of the aluminum current collector provided by LiPF6, while leveraging the high dissociation degree and excellent SEI film-forming properties of LiFSI to improve the ionic conductivity and high-temperature stability of the SEI film, thereby enhancing the overall performance of the battery. However, when the LiFSI lithium salt concentration exceeds 0.4 M, the high-temperature stability of the battery is significantly affected, failing thermal runaway tests. Therefore, the use of LiFSI is limited to this range.

[0040] Furthermore, the positive electrode comprises at least one active material selected from phosphate compounds and lithium-nickel transition metal oxides, wherein the lithium-nickel transition metal oxide has the chemical formula LiNi. m Co n A (1-m-n) As shown in O2, A is selected from at least one of manganese, aluminum, magnesium, chromium, calcium, zirconium, molybdenum, silver, or niobium, 0.5≤m≤1, 0≤n≤0.5, m+n≤1, and / or; the chemical formula of the phosphate compound is as shown in LiMn k B (1-k) As shown in PO4, where 0≤k≤1, and element B is selected from at least one of iron, cobalt, magnesium, calcium, zinc, chromium, or lead.

[0041] In some embodiments, m is a range of 0.55, 0.6, 0.65, 0.7, 0.75, 0.8, 0.85, 0.9, 0.95, or any combination of these values. In some embodiments, n is a range of 0.05, 0.1, 0.15, 0.2, 0.25, 0.3, 0.35, 0.4, 0.45, or any combination of these values. In some embodiments, the lithium nickel transition metal oxide includes at least one of NCA, NCM111, NCM523, NCM622, NCM811, Ni90, Ni92, or Ni95.

[0042] In some embodiments, k is a range of 0.1, 0.15, 0.2, 0.25, 0.3, 0.35, 0.4, 0.45, 0.5, 0.55, 0.6, 0.65, 0.7, 0.75, 0.8, 0.85, 0.9, 0.95, or any combination of these values. In some embodiments, the phosphate compound includes lithium iron phosphate, LiMn... 0.6 Fe 0.4 PO4 or LiMn 0.8 Fe 0.2 At least one of PO4.

[0043] In some embodiments, the positive electrode active material layer further includes a binder, and optionally a conductive agent. The binder improves the bonding between the positive electrode active material particles and also improves the bonding between the positive electrode active material and the current collector.

[0044] In some embodiments, the adhesive includes, but is not limited to: polyvinyl alcohol, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, polymers containing ethylene oxide, polyvinylpyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, acrylated styrene-butadiene rubber, epoxy resin or nylon, etc.

[0045] In some embodiments, the conductive agent includes, but is not limited to, carbon-based materials, metal-based materials, conductive polymers, and mixtures thereof. In some embodiments, the carbon-based material is selected from natural graphite, synthetic graphite, carbon black, acetylene black, Ketjen black, carbon fiber, or any combination thereof. In some embodiments, the metal-based material is selected from metal powder, metal fiber, copper, nickel, aluminum, or silver. In some embodiments, the conductive polymer is a polyphenylene derivative.

[0046] In some embodiments, the positive electrode further includes a positive current collector, which may be a metal foil or a composite current collector. For example, aluminum foil may be used. The composite current collector may be prepared by a process of forming a metallic material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver, and silver alloy, etc.) on a polymer substrate.

[0047] Furthermore, the negative electrode active material includes a carbon material, which includes at least one of natural graphite, artificial graphite, and hard carbon material; and a composite material of carbon material and silicon-based material, which includes at least one of silicon, silicon alloy, silicon oxide, and silicon carbide. Based on the mass of the negative electrode active material, the mass content (g%) of the silicon-based material satisfies: 0 ≤ g ≤ 100.

[0048] In some embodiments, g is a range of 11, 13, 15, 20, 25, 30, 35, 40, 45, 50, 55, 60, 65, 70, 75, 80, 85, 90, 95, or any combination of these values. In some embodiments, 10 ≤ g ≤ 50. In other embodiments, 12 ≤ g ≤ 35.

[0049] In some embodiments, the negative electrode active material layer further includes a binder and a conductive agent. In some embodiments, the binder includes, but is not limited to: polyvinyl alcohol, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, polymers containing ethylene oxide, polyvinylpyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, acrylated styrene-butadiene rubber, epoxy resin, or nylon, etc.

[0050] In some embodiments, the conductive agent includes, but is not limited to, carbon-based materials, metal-based materials, conductive polymers, and mixtures thereof. In some embodiments, the carbon-based material is selected from natural graphite, synthetic graphite, carbon black, acetylene black, Ketjen black, carbon fiber, or any combination thereof. In some embodiments, the metal-based material is selected from metal powder, metal fiber, copper, nickel, aluminum, or silver. In some embodiments, the conductive polymer is a polyphenylene derivative.

[0051] In some embodiments, the negative electrode further includes a negative electrode current collector, which includes: copper foil, nickel foil, stainless steel foil, titanium foil, nickel foam, copper foam, a polymer substrate coated with a conductive metal, or any combination thereof.

[0052] In some embodiments, a separator is provided between the positive and negative electrodes to prevent short circuits. The material and shape of the separator used in the embodiments of this application are not particularly limited, and can be any technology disclosed in the prior art. In some embodiments, the separator comprises a polymer or inorganic material formed from a material stable to the electrolyte of this application.

[0053] For example, the separator may include a substrate layer and a surface treatment layer. The substrate layer is a nonwoven fabric, membrane, or composite membrane with a porous structure, and the material of the substrate layer includes at least one of polyethylene, polypropylene, polyethylene terephthalate, or polyimide. Specifically, a polypropylene porous membrane, a polyethylene porous membrane, a polypropylene nonwoven fabric, a polyethylene nonwoven fabric, or a polypropylene-polyethylene-polypropylene porous composite membrane may be selected.

[0054] A surface treatment layer is disposed on at least one surface of the substrate layer. The surface treatment layer may be a polymer layer or an inorganic layer, or a layer formed by mixing polymers and inorganic substances.

[0055] The inorganic layer comprises inorganic particles and a binder. The inorganic particles include at least one of alumina, silicon oxide, magnesium oxide, titanium oxide, hafnium dioxide, tin oxide, cerium dioxide, nickel oxide, zinc oxide, calcium oxide, zirconium oxide, yttrium oxide, silicon carbide, boehmite, aluminum hydroxide, magnesium hydroxide, calcium hydroxide, or barium sulfate. The binder includes at least one of polyvinylidene fluoride, a copolymer of polyvinylidene fluoride and hexafluoropropylene, polyamide, polyacrylonitrile, polyacrylate, polyacrylic acid, polyacrylate, polyvinylpyrrolidone, polyvinyl ether, polymethyl methacrylate, polytetrafluoroethylene, or polyhexafluoropropylene.

[0056] The polymer layer contains a polymer, the polymer material of which includes at least one of polyamide, polyacrylonitrile, acrylate polymer, polyacrylic acid, polyacrylate, polyvinylpyrrolidone, polyvinyl ether, polyvinylidene fluoride, or poly(vinylidene fluoride-hexafluoropropylene).

[0057] In some embodiments, the method for preparing the secondary battery includes providing electrode assemblies, electrolyte injection, encapsulation, and formation. In some embodiments, the formation temperature is between 30°C and 60°C, for example, 30°C, 32°C, 35°C, 38°C, 41°C, 42°C, 43°C, 44°C, 45°C, 46°C, 47°C, 48°C, or 49°C. In some embodiments, the formation temperature is 40-50°C. In some embodiments, the formation charging current is 0.05C-0.1C, and the formation discharging current is 0.1C-0.3C.

[0058] In some embodiments, the formation includes: charging to 4.2V at a temperature of 40°C-50°C, for example 45°C, with a current of 0.05C and resting for 60 minutes, followed by charging to 4.2V at 0.1C and then discharging to 3.0V at 0.2C.

[0059] In some embodiments, the secondary battery is a lithium secondary battery or a sodium secondary battery. In some embodiments, the lithium secondary battery includes, but is not limited to, a lithium metal secondary battery, a lithium-ion secondary battery, a lithium polymer secondary battery, or a lithium-ion polymer secondary battery.

[0060] In some embodiments, the secondary battery may include an outer packaging, which may be a rigid shell, such as a hard plastic shell, an aluminum shell, or a steel shell. The outer packaging may also be a soft pack, such as a pouch. The soft pack may be made of plastic, such as one or more of polypropylene (PP), polybutylene terephthalate (PBT), and polybutylene succinate (PBS).

[0061] In some embodiments, the shape of the secondary battery is not particularly limited; it can be cylindrical, square, or any other arbitrary shape.

[0062] In some embodiments, this application also provides a battery module. This battery module includes the aforementioned secondary battery. The battery module of this application uses the aforementioned secondary battery, and therefore has at least the same advantages as the aforementioned secondary battery. The battery module of this application can contain multiple secondary batteries, and the specific number can be adjusted according to the application and capacity of the battery module.

[0063] In some embodiments, this application also provides a battery pack including the aforementioned battery modules. The number of battery modules included in the battery pack can be adjusted according to the application and capacity of the battery pack.

[0064] In a second aspect, the present invention also provides an electrical device comprising the secondary battery described in any one of the first aspects.

[0065] In some embodiments, the electrical equipment includes: electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, energy storage systems, etc. To meet the device's requirements for high power and high energy density of the secondary battery, a battery pack or battery module can be used.

[0066] In other embodiments, the device may be a mobile phone, tablet computer, laptop computer, etc. This device typically requires a slim and lightweight design and may use a rechargeable battery as its power source.

[0067] Compared with the prior art, the beneficial technical effects of this invention are reflected in: The secondary battery of this application optimizes the composition and structure of the negative electrode interface film by controlling the ratio of the two types of sulfur elements present in the negative electrode SEI film, thereby obtaining a dense, stable, and highly ionicly conductive interface film, improving the battery's fast charging rate performance. At the same time, it effectively suppresses the continuous side reaction between the electrolyte and the negative electrode active material, reduces the electrolyte consumption rate, and thus improves the secondary battery's room temperature cycle performance, high temperature storage performance, and high temperature stability. Attached Figure Description

[0068] Figure 1 The image shows the X-ray photoelectron spectroscopy (XPS) spectrum of the solid electrolyte interface film on the surface of the negative electrode sheet provided in Embodiment 2 of the present invention. Figure 2 The image shows the X-ray photoelectron spectroscopy (XPS) spectrum of the solid electrolyte interface film on the surface of the negative electrode sheet provided in Embodiment 13 of the present invention. Detailed Implementation

[0069] To make the above-mentioned objects, features and advantages of the present invention more apparent and understandable, the specific embodiments of the present invention will be described in detail below with reference to the accompanying drawings.

[0070] Many specific details are set forth in the following description in order to provide a full understanding of the invention. However, the invention may also be practiced in other ways different from those described herein, and those skilled in the art can make similar extensions without departing from the spirit of the invention. Therefore, the invention is not limited to the specific embodiments disclosed below.

[0071] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The phrase "in one embodiment" appearing in different places in this specification does not necessarily refer to the same embodiment, nor is it a single or selective embodiment that excludes other embodiments. Where specific conditions are not specified in the embodiments, conventional conditions or conditions recommended by the manufacturer shall be followed. Where the manufacturers of reagents or instruments are not specified, they are all conventional products that can be purchased commercially.

[0072] The embodiments of the present invention will be described in detail below with reference to the accompanying drawings.

[0073] Example 1 The cathode preparation steps are as follows: The cathode active material LiNi is prepared... 0.9 Co 0.05 Mn 0.05 O2, a mixture of conductive agent carbon nanotubes / acetylene black, and binder polyvinylidene fluoride (PVDF), in the following weight ratios: LiNi 0.9 Co 0.05 Mn 0.05O2:CNT / Super-P:PVDF=95:(2.0 / 1.0):2 was thoroughly homogenized in an N-methylpyrrolidone (NMP) solvent system, coated onto a 12μm thick aluminum-coated current collector, dried, and rolled to obtain a positive electrode sheet with a porosity of 25.4%.

[0074] The anode preparation steps are as follows: Silicon-oxygen (SiO2) is used as the anode active material. x A graphite composite (with a silicon-to-graphite mass ratio of 14:86), conductive agent acetylene black, binder styrene-butadiene rubber (SBR), thickener sodium carboxymethyl cellulose (CMCNa), and polyacrylic acid (PAA) were mixed in deionized water at a weight ratio of 96:2:1.5:1:0.5. The mixture was then coated onto the surface of an 8μm thick copper current collector. After drying, rolling, and slitting, a negative electrode sheet was obtained, with a negative electrode porosity of 33.5%.

[0075] The diaphragm is a three-layer composite PP / PE / PP membrane.

[0076] Electrolyte preparation: In an argon-filled glove box (H2O < 0.1 ppm, O2 < 0.1 ppm), lithium salts LiPF6 and LiFSI and solvents EC / DMC / EA = 30 / 55 / 15 (mass ratio) were mixed evenly according to the proportions shown in Table 1 to prepare a solution with a lithium salt concentration of 1 M. Finally, sulfur-containing compound additives and other additives in Table 1 were added and stirred evenly to obtain the lithium-ion battery electrolyte of Example 1.

[0077] Preparation of lithium-ion batteries: The prepared positive electrode sheet, separator, and negative electrode sheet are stacked in sequence, with the separator in the middle of the positive and negative electrode sheets, and wound to obtain a bare cell; the bare cell is placed in an aluminum-plastic film outer packaging, and after being fully dried, it is injected with the prepared lithium-ion battery electrolyte. The battery is then subjected to a 48-hour rest at 45°C, high-temperature fixture formation (formation conditions are: temperature 45°C, 0.05C current charging to 4.2V, standing for 60 minutes, then 0.1C charging to 4.2V, then 0.2C discharging to 3.0V, and so on, repeated twice) and secondary sealing, followed by conventional capacity testing.

[0078] Examples 2 to 20 and Comparative Examples 1 to 8 Examples 2 to 20 and Comparative Examples 1 to 8 were achieved by adjusting the electrolyte ratio, the OI value of the negative electrode, and the formation conditions based on Example 1. Specific adjustment measures and detailed data are shown in Table 1.

[0079] Table 1

[0080] It should be noted that "low viscosity solvent %" in Table 1 refers to the mass percentage of low viscosity solvent among all solvents; in Examples 12 and 13, the EA content was adjusted to 10% and 20% respectively, and the total solvent ratio was adjusted accordingly to EC / DMC / EA = 30 / 60 / 10 and 30 / 50 / 20, that is, keeping the EC percentage unchanged and adjusting the ratio of DMC to EA. The "sulfide A%", "sulfide B%", and "other additives %" in Table 1 are all mass percentages calculated based on the total mass of the electrolyte; "lithium salt ratio LiPF6 / LiFSI" is a molar ratio.

[0081] Test methods 1. Determination of OI value of graphite negative electrode The orientation index (OI) of graphite anodes is a key parameter describing the degree of orderliness of graphite sheet arrangement, and it is determined by X-ray diffraction (XRD). Test procedure: The graphite anode sheet is cut into 2cm × 2cm pieces and fixed on the XRD sample stage; the scanning angle range is set to 10°-90°, and the scanning rate is 5° / min, for diffraction testing. Result calculation: The orientation index is calculated using the peak intensity ratio OI = I(004) / I(110), and this ratio represents the OI value of the graphite anode.

[0082] 2. First Coulomb Efficiency Test of Battery At 25°C, the lithium-ion secondary battery was charged at a constant current of 1C to 4.2V, followed by constant voltage charging until the current was less than 0.05C, and the initial charge capacity was recorded. After resting for 5 minutes, it was discharged at a constant current of 1C to 2.5V, and the initial discharge capacity was recorded. The initial coulombic efficiency of the lithium-ion secondary battery = initial discharge capacity / initial charge capacity × 100%.

[0083] 3. Battery cycle capacity retention test At 25°C, the lithium-ion battery was charged at a constant current of 1C to 4.25V, then charged at a constant voltage of 4.25V to 0.05C, and then discharged at a constant current of 1C to 2.5V. After 1000 charge-discharge cycles, the capacity retention rate after the 1000th cycle at 25°C was calculated using the following formula: Discharge capacity after 1000th cycle / Discharge capacity of the first cycle × 100%.

[0084] At 50°C, the lithium-ion battery was charged at a constant current of 1C to 4.25V, then charged at a constant voltage of 4.25V to 0.05C, and then discharged at a constant current of 1C to 2.5V. After 500 charge-discharge cycles, the capacity retention rate at 50°C and after the 500th cycle was calculated using the following formula: Discharge capacity after the 500th cycle / Discharge capacity of the first cycle × 100%.

[0085] 4. Battery thickness change rate at 50℃ storage The battery was discharged at 25℃ with a constant current of 0.5C to 3.0V, then charged at a constant current of 0.5C to 4.45V, and then charged at a constant voltage of 4.45V to 0.05C. The thickness of the battery at this point was measured using a PPG soft-pack battery thickness gauge and recorded as 'a'. The battery was then placed in an oven and stored at 50℃ with a constant voltage of 4.45V for 21 days. The thickness after 21 days was recorded as 'b'. The formula for calculating the thickness expansion rate is: (ba) / a × 100%.

[0086] 5. Test of sulfur elemental composition content in SEI membrane The lithium-ion battery was discharged to 2.5V at 0.1C, and the electrode sheets were obtained by disassembling the lithium-ion battery in an argon-filled glove box. The obtained electrode sheets were cut into 8mm × 8mm test samples and immersed in a low-boiling-point dimethyl carbonate (DMC) solvent for half an hour. After complete drying, they were attached to the XPS sample stage with the surface of the positive or negative active material layer facing upwards, away from the current collector. Measurements were performed without exposure to the atmosphere. Specific test conditions and procedures are as follows: Single-crystal AlKα X-ray spectroscopy was used. For X-ray points, an elliptic pattern of 1000 × 1750 μm with an output of 10 kV and 22 mA was used. Data was selected at a sputtering etching time of 0 seconds. For neutral carbon C1s, 284.8 eV was used. Data processing, such as peak differentiation, employed three-point smoothing, peak area measurement, background subtraction, and peak synthesis to calculate the percentage content of sulfur in the negative electrode SEI. Li₂SO₄... x The position of (x=3 or 4) is ~169 eV, while the position of the organic sulfonate lithium RSO3Li is ~166.5 eV.

[0087] Test Results The battery performance test results of Examples 1-20 and Comparative Examples 1-8 are shown in Table 2 and Figure 1 , Figure 2 .

[0088] Table 2

[0089] As shown in Tables 1 and 2, the initial coulombic efficiency of each embodiment is 84%~92%, the capacity retention rate after 1000 cycles at 25°C is 84%~94%, the capacity retention rate after 500 cycles at 50°C is 84%~92%, and the thickness change rate after 21 days of storage at 50°C is 1.6%~3.6%, all of which demonstrate excellent fast charging performance, cycle life, and high-temperature storage performance.

[0090] In contrast, the S1 / S2 ratios of Comparative Examples 1-4 were 5, 0.55, 0.71, and 4.09, respectively, all exceeding the range of 1-2.5. Their capacity retention after 1000 cycles at 25°C was only 55%-61%, and their thickness change rate at 50°C was as high as 6.1%-18.9%. The OI values ​​of Comparative Examples 5-6 were 0.21 and 0.45, respectively, and their 10w-S1 / S2 ratios were 0.77 and 2.25, both exceeding the range of 1-2. Their initial coulombic efficiency was only 70% and 73%, respectively, indicating significant degradation in high-temperature storage performance. Comparative Examples 7-8, using excessively high formation temperatures (70°C) or excessively high formation currents (0.5-1.0C charge / 1.0C discharge), also experienced severe performance degradation. The above comparative data show that only when both S1 / S2 and 10w-S1 / S2 simultaneously meet the ranges defined in this application can the fast-charging performance, cycle life, and high-temperature storage performance of the secondary battery be balanced.

[0091] Furthermore, a comparison of Examples 4 and 9-10 shows that the battery performance is further improved when sulfur-containing additives are used in combination with VC or FEC. Examples 11-13 show that when the content of the low-viscosity solvent EA increases from 10% to 20%, the cycle retention rate increases from 86% to 94%, and the thickness change rate decreases from 2.1% to 1.6%. Examples 14-15 show that appropriately increasing the LiFSI ratio also helps improve battery performance. These results demonstrate that this application successfully achieves a synergistic improvement in battery fast-charging performance, cycle life, and high-temperature stability by introducing sulfur-containing additives into the electrolyte and synergistically controlling the proportion of specific sulfur-containing components in the SEI film and the negative electrode OI value.

[0092] like Figure 1 and Figure 2 The images shown are X-ray photoelectron spectroscopy (XPS) spectra of the solid electrolyte interphase (SEI) film on the surface of the negative electrode active material layer in Examples 2 and 13 of this application, respectively. The peaks in the spectra located near the binding energy of ~169 eV correspond to the inorganic sulfide Li₂SO₄. x (x=3 or 4), its sulfur content is denoted as S1; the peak located near the binding energy of ~166.5 eV corresponds to the organic sulfonate lithium RSO3Li, and its sulfur content is denoted as S2. Among these, Figure 1 The corresponding S1 / S2 ratio is 1.57; Figure 2 The corresponding S1 / S2 ratio is 2.08. Figure 1-2 This demonstrates that by adding specific sulfur-containing additives to the electrolyte of this application and combining it with a corresponding formation process, it is possible to successfully construct a cathode containing Li2SO4 on its surface. x It can be used to make SEI films of RSO3Li and can effectively control the content ratio of the two.

[0093] The above detailed description is a specific description of one of the feasible embodiments of the present invention. This embodiment is not intended to limit the patent scope of the present invention. All equivalent implementations or modifications that do not depart from the present invention should be included within the scope of the technical solution of the present invention.

[0094] It should be particularly noted that the various embodiments listed in this specification and accompanying drawings are intended to illustrate the technical solutions and advantages of the present invention, and not to limit the scope of protection of the present invention. Without departing from the core ideas and technical effects of the present invention, those skilled in the art can make any form of improvement, substitution, combination, or modification to the structural arrangement, process parameters, material selection, control logic, etc., of the described embodiments; any obvious changes based on the same concept should be considered equivalent solutions of the present invention and should be included within the scope of protection defined by the claims of the present invention. The actual scope of protection of the present invention is determined by the appended claims and should be correctly understood in conjunction with the specification and accompanying drawings.

Claims

1. A secondary battery, comprising a positive electrode, a negative electrode, and an electrolyte, characterized in that, The negative electrode includes a negative electrode active material layer and an SEI film located on the surface of the negative electrode active material layer, wherein the SEI film contains Li₂SO₄. x And organic lithium sulfonates RSO3Li, Li2SO x In Li₂SO₃Li, x is 3 or 4, and R is a C1-C6 alkyl or alkenyl group. x The sulfur content in RSO3Li is S1%, and the sulfur content in RSO3Li is S2%, where 1≤S1 / S2≤2.5; The OI value of the negative electrode is w, 1≤10w-S1 / S2≤2.

2. The secondary battery according to claim 1, characterized in that, 0 < S1 ≤ 10; 0 < S2 ≤ 4.

3. The secondary battery according to claim 2, characterized in that, 1≤S1≤5; 0<S2≤2.

4. The secondary battery according to claim 1, characterized in that, 0.25≤w≤0.40。 5. The secondary battery according to claim 1, characterized in that, The electrolyte includes a sulfur-containing additive, which includes at least one of sulfonates, sulfates, sulfites, polycyclic sulfites, and polycyclic sulfites.

6. The secondary battery according to claim 5, characterized in that, The sulfonate includes at least one of the compounds shown in Formula I-1 and Formula I-2. Equation I-1, Equation I-2, In Formula I-1, Q1 and Q2 are independently selected from C1-C6 alkylene groups; In Formula I-2, R1 and R2 are independently selected from hydrogen atoms or C1-C6 alkyl groups, and Q3 is selected from C1-C6 alkylene groups or C2-C6 alkenyl groups.

7. The secondary battery according to claim 5, characterized in that, The sulfate ester includes at least one of the compounds shown in Formula I-3. Formula I-3, In Formula I-3, R3, R4, R5, and R6 are independently selected from hydrogen atoms or C1-C6 alkyl groups, and Q4 is absent or selected from C1-C6 alkylene groups.

8. The secondary battery according to claim 5, characterized in that, The sulfite includes at least one of the compounds shown in Formula I-4 and Formula I-5. Equation I-4, Equation I-5, In Equation I-4, R7, R8, R9, R 10 Independently selected from hydrogen atoms or C1-C6 alkyl groups, Q5 is absent or Q5 is selected from C1-C6 alkylene groups; In Equation I-5, R 11 and R 12 It is independently selected from C1-C6 alkyl groups.

9. The secondary battery according to claim 5, characterized in that, The polycyclic sulfides and / or polycyclic sulfites include at least one of the compounds shown in formulas I-6 to I-11. In formulas I-6~I-11, R 13 ~R 24 It is independently selected from hydrogen atoms or C1-C6 alkyl or C1-C6 alkenyl groups.

10. The secondary battery according to claim 5, characterized in that, The sulfonate comprises at least one of methyl disulfonate, ethyl disulfonate, propylene disulfonate, 1,3-propanesulfonyl lactone, 1-propylene-1,3-sulfonyl lactone, and 1,4-butanesulfonyl lactone, and / or the sulfate comprises at least one of vinyl sulfate, 4-methyl ethylene sulfate, 4-ethyl ethylene sulfate, 4-propyl ethylene sulfate, and propylene sulfate, and / or the sulfite comprises at least one of ethylene sulfite, dimethyl sulfite, and diethyl sulfite.

11. The secondary battery according to claim 9, characterized in that, The polycyclic cyclic sulfates and / or polycyclic sulfites include at least one of pentaerythritol bicyclic sulfate, 4,4'-bis-1,2-oxothiane, 2,2,2',2'-tetraoxide, glyoxal sulfate, ethylene disulfate, ethylene trisulfate, and mannitol ethylene carbonate sulfate.

12. The secondary battery according to claim 5, characterized in that, Based on the mass of the electrolyte, the mass content of the sulfur-containing additive is 0.5%-4%.

13. The secondary battery according to claim 1, characterized in that, The electrolyte also includes other additives, including at least one of vinylene carbonate, ethylene ethylene carbonate, lithium difluorophosphate, and fluoroethylene carbonate; the mass content of the other additives is 0.1%-10% based on the mass of the electrolyte.

14. The secondary battery according to claim 1, characterized in that, The electrolyte includes a carbonate solvent and a low-viscosity solvent; The carbonate solvent includes at least one of ethylene carbonate EC, dimethyl carbonate DMC, and ethyl methyl carbonate EMC; The low-viscosity solvent has a viscosity ≤0.6 cP and is selected from at least one of carboxylic acid ester solvents and nitrile solvents; The low-viscosity solvent includes at least one of methyl acetate, ethyl acetate, ethyl propionate, and acetonitrile.

15. The secondary battery according to claim 1, characterized in that, The electrolyte comprises LiPF6 and LiFSI, and satisfies N (LiPF6) >N (LiFSI) 0.8M≤N (LiPF6) +N (LiFSI) ≤1.5M, 0<N (LiFSI) <0.4M, where N (LiPF6) and N (LiFSI) These represent the molar concentrations of LiPF6 and LiFSI based on the electrolyte, respectively.

16. The secondary battery according to claim 1, characterized in that, The positive electrode comprises at least one active material selected from phosphate compounds and lithium-nickel transition metal oxides, wherein the lithium-nickel transition metal oxide has the chemical formula LiNi. m Co n A (1-m-n) As shown in O2, A is selected from at least one of manganese, aluminum, magnesium, chromium, calcium, zirconium, molybdenum, silver, or niobium, 0.5≤m≤1, 0≤n≤0.5, m+n≤1, and / or; the chemical formula of the phosphate compound is as shown in LiMn k B (1-k) As shown in PO4, where 0≤k≤1, and element B is selected from at least one of iron, cobalt, magnesium, calcium, zinc, chromium, or lead.

17. The secondary battery according to claim 1, characterized in that, The negative electrode active material includes carbon materials, which include at least one of natural graphite, artificial graphite, and hard carbon materials; and a composite material of carbon materials and silicon-based materials, which includes at least one of silicon, silicon alloys, silicon oxides, and silicon-carbon compounds. Based on the mass of the negative electrode active material, the mass content (g%) of the silicon-based material satisfies: 0 ≤ g ≤ 100.

18. An electrical appliance, characterized in that, The secondary battery includes any one of claims 1 to 17.